Financial Literacy Persuasion for Early Chilhood in Kuyudan Baru Makamhaji - Minhayati Saleh; Mardalis, Ahmad; Syamsilasmi Saleh (Universitas Muhammadiyah Surakarta, 2025)
Financial literacy education for children is not only limited to introducing money, but also a concept about introducing wise financial management. Children are trained to have the ability to control financial spending. This community service aims to instill the importance of managing finances and instill effective financial literacy values in them. The training was attended by 22 children studying at elementary and kindergarten levels. The method of implementing this community service is awareness by showing financial literacy videos. Participants are given a sum of money which is then asked about the use of the money if they have money. After the screening, it is continued with an explanation and reflection. To determine the understanding of the training participants, a pre-test and post-test were conducted. The results showed an increase in the financial understanding of the training participants.